Higher order Galilean invariant Lattice Boltzmann method - Wahyu Perdana Yudistiawan (2013)
With the increase of microfluidics applications in recent years, there has been more emphasis given to find alternative modeling method in the microflow regime where the classical Navier-Stokes model broke down. In this regime, the mean-free path of a particle is comparable to the characteristic size of the channel, giving the boundary interaction a major role to play. While methods such as molecular dynamics and Monte-Carlo are excellent for simulating transitional regime, the computational cost is too expensive to be used for any realistic simulation in near continuum sub-sonic regime.